Efektivitas Kemampuan Kerja Terhadap Semangat Kerja pada PT Doosan Jaya Sukabumi - Restiani, Resta; Mulia, Faizal; Jhoansyah, Dicky (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2020)
The development of the company PT Doosan Jaya Sukabumi increases the decrease in work ability or increase work in work ability not all employees need skills and conversely all employees do not all have great morale. Because this research has goals to be achieved as well. In this study to process data, the researchers used quantitative methods with associative approach, and researchers tested 100 respondents for the employees of PT. Doosan Jaya Sukabumi to produce data on the company. T-test results show the ability of work in this study was 9,280 with a significant value of 0,000, then a significant value of 0,000 <compared to 0.05, it can be concluded that the variable work ability increased positively on morale. at PT. Doosan Jaya Sukabumi.